Isolated palpitations and ventricular pre‐excitation. Issue 4 (13th May 2020) - Arias, Miguel A.; Pachón, Marta; Martín‐Sierra, Cristina
Abstract : A 27‐year‐old male was referred for further assessment after being evaluated by his general practitioner for isolated palpitations. A twelve‐lead electrocardiogram was performed in which sinus rhythm with ventricular pre‐excitation were observed. Electrophysiologic study demonstrated the presence of a fasciculoventricular accessory pathway.